2006
DOI: 10.1540/jsmr.42.33
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic component of the temperature-sensitivity of slow waves recorded from gastric muscle of the guinea-pig

Abstract: The effects of changes in temperature on slow waves were investigated in smooth muscle tissues isolated from the guinea-pig gastric antrum. Within the range 24°C to 42°C, elevation of temperature increased the frequency and maximum rate of rise of the upstroke phase (dV/dt) of slow waves and decreased their duration, with no alteration to amplitude or resting membrane potential. These observations also applied to follower potentials and pacemaker potentials recorded from longitudinal muscle and myenteric inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…These values were comparable to those reported previously by Dickens et al (1999) and Nakamura et al (2006). The I-D relationship was measured in all preparations, and one of the typical examples was shown in Fig.…”
Section: Properties Of Follower Potentialsupporting
confidence: 90%
See 1 more Smart Citation
“…These values were comparable to those reported previously by Dickens et al (1999) and Nakamura et al (2006). The I-D relationship was measured in all preparations, and one of the typical examples was shown in Fig.…”
Section: Properties Of Follower Potentialsupporting
confidence: 90%
“…Isolated gastric smooth muscle generates slow waves in circular muscle cells or follower potentials in longitudinal muscle cells, in response to pacemaker potentials generated in ICC-MP (Dickens et al, 1999;Dickens et al, 2001). The occurrence of individual pacemaker potentials is not constant, and it is a function of temperature, membrane potential and activities of intracellular components such as endoplasmic reticulum (ER) and mitochondria (Nose et al, 2000;Ward et al, 2003;Ward et al, 2004;Nakamura et al, 2006;Suzuki et al, 2006;Kito and Suzuki, 2007;Nakamura et al, 2009). The duration of pacemaker potential is also not homogeneous, and it is shown by Hirst and Edwards (2001) that in smooth muscle segments isolated from the guinea-pig stomach, the duration of driving potential (equal to pacemaker potential) is a function of time required for the generation of the potential after termination of the previous potential, i.e., there is a linear relationship between the time for the interval between pacemaker potentials and the duration of subsequently generated pacemaker potential.…”
Section: Introductionmentioning
confidence: 99%
“…This peristaltic contraction has been demonstrated to be influenced by temperature. A reduction in temperature decreases the propagation rate of slow waves [40], and an increase in temperature increases the frequency and maximum rising rate of the upstroke phase in experimental animals [41]. In a human study, Sun et al [1] found that cold (4°C) or hot (50°C) meals caused the suppression of antral pressure waves and the acceleration of isolated pyloric pressure waves.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of slow waves is very sensitive to changes in temperature, a high temperature coefficient ( Q 10 ) for slow waves has been reported in the guinea‐pig stomach (Ohba et al 1977; Tomita, 1981; Nakamura et al 2006). The duration, rate of rise of the upstroke phase and frequency of slow waves all show marked temperature sensitivity ( Q 10 > 2; Fig.…”
Section: Factors Modifying the Frequency Of Spontaneous Activitymentioning
confidence: 99%